The Influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), BI Rate and Inflation on Return on Assets (ROA) in BUMN Banking (BRI, Mandiri, BNI & BTN) Period 2014 –2019 - RizkyAkbar; Sugiharto; Rasyidi; NoorHidayati (Magister Administrasi Bisnis ULM, 2024)
Abstract: This study aims to determine and examine the effect of the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), BI Rate and Inflation on Return on Assets (ROA) in BUMN Banking (BRI, Mandiri, BNI & BTN) Period 2014 – 2019.The research approach used is a quantitative approach. The type of research is associative research with a causal relationship, the sample used is 24 financial statement data with purposive sampling technique. Using quantitative data and data collection using secondary data, while data analysis using multiple linear regression with SPSS version 25.0 application tools. The results of the study partially prove that the Capital Adequacy Ratio (CAR)has a significant effect on Return On Assets (ROA) with a large effect of 18.73%, Loan to Deposit Ratio (LDR) has a significant effect on Return On Assets (ROA) with a large influence of 40.40%, Non-Performing Loans (NPL) has a significant effect on Return On Assets (ROA) with a large effect of 20.10% and the BI Rate has a significant effect on Return On Assets (ROA) with a large effect of 5.10%. While inflation partially does not have a significant effect on Return on Assets (ROA) with a large effect of 5.23%. However, simultaneously the variables of Capital Adequacy Ratio (CAR), Non performing Loan (NPL), Loan to Deposit Ratio (LDR), BI Rate and Inflation have a significant effect on Return on Assets (ROA) with a contribution of 88.8%